Detection of encapsulation in Staphylococcus aureus by use of antiserum agar. - West, T E (1984)
We examined an antiserum agar method to study its reliability in screening Staphylococcus aureus strains for capsule production. The encapsulated S. aureus Smith diffuse strain was compared with its nonencapsulated variant, Smith compact, in CCY medium containing 0.5% NaCl and 5.0% Smith diffuse rabbit antiserum. A halo was visible surrounding colonies of the Smith diffuse strain but not the Smith compact strain. On this same medium, the protein A-producing Cowan I strain possessed a halo that was visible on photographs. Single high-salt medium is known to inhibit protein A production, halo formation by the strains was also compared in 7.5% NaCl medium. The halo surrounding the Cowan I strain was not present when the salt content of the medium was increased. In contrast, the halo surrounding the Smith diffuse strain persisted in the 7.5% NaCl medium. By use of this medium, the antiserum agar technique may be valuable for the identification of encapsulated staphylococci without appreciable interference from protein A.